Isolation, Characterization, and Assessment of Probiotic Lactococcus lactis from the Intestinal Tract of Largemouth Bass (Micropterus salmoides) - Xiaoyu Chen; Jiaonan Zhang; Jiaolin Zhang; Wenzheng Zou; Qingpi Yan (Fishes)
The health benefits associated with microbial species inhabiting aquatic animals have garnered increasing attention, as it is expected that the colonization and efficacy of native probiotic bacteria adapted to the internal environment of the target species will be more active than non-native bacteria. In this study, six isolates were obtained from the intestinal tract of largemouth bass. Three of these isolates demonstrated higher growth ability compared to the others and were further characterized using in vitro assays. Lactococcus lactis LBM15 was found to exhibit antibacterial activity against common pathogens affecting largemouth bass; the adhesion inhibition capabilities of the isolates were systematically evaluated through competitive, repulsive, and substitutive adhesion assays. The strain inhibited adhesion to all six tested pathogen strains, with competitive adhesion inhibition rates ranging from 42% to 54%, the highest of which was observed against V. anguillarum. Repulsive adhesion inhibition rates ranged from 27% to 55%, with the highest rate noted for Edwardsiella tarda. Additionally, substitutive adhesion inhibition rates were found to range from 48% to 76%, with the highest inhibition observed against Aeromonas hydrophila. Furthermore, LBM15 exhibited favorable antimicrobial susceptibility profiles, showing sensitivity to 21 antibiotics tested. Notably, safety assessment trials were performed exposing fish to LBM15 at a concentration of 1 × 109 CFU/mL by injection and at a concentration of 1 × 108 CFU/mL by feed administration. No clinical abnormalities, behavioral alterations, or mortality were documented in either exposure group, confirming the safety of LBM15 for application in aquaculture. The results suggested that LBM15 isolates from largemouth bass have potential for further investigation and possible application as probiotic candidates.